2019
DOI: 10.1111/eje.12447
|View full text |Cite
|
Sign up to set email alerts
|

Exploring training dental implant placement using computer‐guided implant navigation system for predoctoral students: A pilot study

Abstract: Introduction:Recent computer-guided dynamic navigation systems promise a novel training approach for implant surgery. This study aimed to examine learning progress in placement of dental implants among dental students using dynamic navigation on a simulation model. Materials and Methods:Senior students with no implant placement experience were randomly assigned five implant placement attempts involving either three maxillary or four mandibular implants distributed in the anterior/posterior, and left/right segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 20 publications
9
50
1
Order By: Relevance
“…Therefore, we could examine the effect of the demographics of the dentist on the accuracy of static guided implant surgery. For dynamic computer-guided navigation systems, junior dentists or dental students were reported to have better performance in terms of the accuracy of implant placement [26,27]; However, we did not find similar studies for the static guided implant surgery in the literature. The effect of age on the accuracy of static guided implant surgery remains an issue to be clarified.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, we could examine the effect of the demographics of the dentist on the accuracy of static guided implant surgery. For dynamic computer-guided navigation systems, junior dentists or dental students were reported to have better performance in terms of the accuracy of implant placement [26,27]; However, we did not find similar studies for the static guided implant surgery in the literature. The effect of age on the accuracy of static guided implant surgery remains an issue to be clarified.…”
Section: Discussionmentioning
confidence: 65%
“…However, in another clinical study, Cassetta et al [33] did not find a clear learning curve after examining 227 implants inserted via bone-, tooth-, and mucosa-supported SLA surgical guides. Nevertheless, in a pilot study on a simulation model to examine the learning progress among dental students, Golob Deeb et al [27] observed a significant improvement in speed and angular accuracy of implant placement using dynamic navigation in the first three implantations. Unfortunately, we did not measure the sequence and time for each implant placement of the operators; hence, the comparison of the improvement within each operator was impossible in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Few in vitro studies involving dynamic navigation systems aim to investigate the relevance of surgical experience in achieving an accurate implant placement [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding drilling time, two published model-based studies investigated the learning curve using dynamic navigation, but they lacked considerations on the influence of surgical experience [12,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation